Fighting for recognition : identity, masculinity and the act of violence in professional wrestling - Smith, R. Tyson (Duke University Press, 2014)
In this riveting ethnography, R. Tyson Smith takes readers into the world of independent professional wrestling, where young men, mostly from mostly working-class suburban backgrounds, compete in community centers, high-school gyms, and other modest venues. Smith considers why many young men choose to compete on independent wrestling circuits, thereby subjecting themselves to ridicule, damaging their bodies and risking their relationships and jobs.